PELAKSANAAN WEWENANG WAKIL PRESIDEN N DALAM PENYELENGGARAAN PEMERINTAHAN - HERMAWAN, BAMBANG (Jurnal Hukum Volkgeist, 2017)
No details the authority owned by the Vice President could potentially lead to legal uncertainty. Whereas in the construction of the position incumbent of the position of the Vice President has a position that is very fundamental research purposes in writing this is to know the authority of the Vice President in the Organization of the Government and To knowing the implementation authority Vice President in organizing the Government. In this study the normative legal research using methods based on relevant legislation and other legal materials related to the substance of the research, then connected with problems in This research. Research results show that the authority of the Vice President is not set explicitly in the legislation. Authority of the Vice President are only found by analyzing the legislation. ' Where there are 3 Vice Presidential Authority: the authority of the Vice President as the representative of the President, the powers of the Vice President As President, the Maid Authority of the Vice President as successor to the President whereas the implementation authority Vice President subject to the authority of the source.  Source  from authority of the attribution of the implementation authority Vice President gained the authority directly by the 1945 Constitution and its implementation without going through intermediaries. For the delegation of authority then the implementation authority in advance must there is a delegation of authority that has the force of law so that the execution of the authority of the Vice-president can be strengthened by positive law in order to set up and defend it.